2018
DOI: 10.1016/j.psychres.2018.03.060
|View full text |Cite
|
Sign up to set email alerts
|

A 12-month study of the hikikomori syndrome of social withdrawal: Clinical characterization and different subtypes proposal

Abstract: Social withdrawal is a new mental health problem increasingly common, present in different cultures, whose psychopathology and treatment is not yet established. This study aims to determine the socio-demographic and clinical features and possible clinical subtypes that predict the 12-month outcomes of cases with hikikomori syndrome, a severe form of social withdrawal. Socio-demographic and clinical data at baseline were analysed as well as data obtained for 12 months after at-home treatment in 190 cases. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 46 publications
3
53
0
Order By: Relevance
“…In 2010, we conducted the first international hikikomori survey targeting psychiatrists in Australia, Bangladesh, Iran, India, Japan, South Korea, Taiwan, Thailand, and the USA using two case vignettes in a self‐reporting format and showed the possibility of a hikikomori ‐like phenomenon in all the countries surveyed . Thereafter, the cases of hikikomori sufferers in countries including France, Spain, Italy and Brazil were reported . Epidemiological surveys of hikikomori outside Japan are very limited.…”
Section: Multidimensional Understandings Of Hikikomorimentioning
confidence: 99%
See 1 more Smart Citation
“…In 2010, we conducted the first international hikikomori survey targeting psychiatrists in Australia, Bangladesh, Iran, India, Japan, South Korea, Taiwan, Thailand, and the USA using two case vignettes in a self‐reporting format and showed the possibility of a hikikomori ‐like phenomenon in all the countries surveyed . Thereafter, the cases of hikikomori sufferers in countries including France, Spain, Italy and Brazil were reported . Epidemiological surveys of hikikomori outside Japan are very limited.…”
Section: Multidimensional Understandings Of Hikikomorimentioning
confidence: 99%
“…9,18 Thereafter, the cases of hikikomori sufferers in countries including France, Spain, Italy and Brazil were reported. [38][39][40][41][42][43][44] Epidemiological surveys of hikikomori outside Japan are very limited. In Hong Kong, a telephone-based epidemiological survey has revealed that hikikomori sufferers (duration 6 months and over) account for 1.9% of the population.…”
Section: Multidimensional Understandings Of Hikikomorimentioning
confidence: 99%
“…Fourth, we have removed other psychiatric disorders as an exclusion criterion for hikikomori. It is clear that this disorder tends to co‐occur with other conditions. In our view, the frequency of co‐occurring conditions increases the importance of addressing social withdrawal as a health issue.…”
mentioning
confidence: 91%
“…Social withdrawal syndrome was first described in Japan as hikikomori, and defined as the state of confining oneself to one's house for more than 6 months and strictly limiting communication with others (1). In recent years its existence has been described in other countries and cultures, noting that other factors besides Japanese culture may also influence its origin and development (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously assessed which factors determine withdrawal relapse or persistence (3). Among them, some factors, such as age or comorbid diagnostics, may result in being difficult to modify.…”
Section: Introductionmentioning
confidence: 99%